p62/SQSTM1 is required for Parkin-induced mitochondrial clustering but not mitophagy; VDAC1 is dispensable for both - Narendra, Derek P (Landes Bioscience, 2010)
Mitochondria sustain damage with aging, and the resulting mitochondrial dysfunction has been implicated in a number of diseases including parkinson disease. We recently demonstrated that the E3 ubiquitin ligase Parkin, which is linked to recessive forms of parkinsonism, causes a dramatic increase in mitophagy and a change in mitochondrial distribution, following its translocation from the cytosol to mitochondria. Investigating how Parkin induces these changes may offer insight into the mechanisms that lead to the sequestration and elimination of damaged mitochondria. We report that following Parkin's translocation from the cytosol to mitochondria, Parkin (but not a pathogenic mutant) promotes the K63-linked polyubiquitination of mitochondrial substrate(s) and recruits the ubiquitin- and LC3-binding protein, p62/SQSTM1, to mitochondria. After its recruitment, p62/SQSTM1 mediates the aggregation of dysfunctional mitochondria through polymerization via its PB1 domain, in a manner analogous to its aggregation of polyubiquitinated proteins. Surprisingly and in contrast to what has been recently reported for ubiquitin-induced pexophagy and xenophagy, p62 appears to be dispensable for mitophagy. Similarly, mitochondrial-anchored ubiquitin is sufficient to recruit p62 and promote mitochondrial clustering, but does not promote mitophagy. Although VDAC1 (but not VDAC2) is ubiquitinated following mitochondrial depolarization, we find VDAC1 cannot fully account for the mitochondrial K63-linked ubiquitin immunoreactivity observed following depolarization, as it is also observed in VDAC1/3(−/−) mouse embryonic fibroblasts. Additionally, we find VDAC1 and VDAC3 are dispensable for the recruitment of p62, mitochondrial clustering and mitophagy. These results demonstrate that mitochondria are aggregated by p62, following its recruitment by Parkin in a VDAC1-independent manner. They also suggest that proteins other than p62 are likely required for mitophagy downstream of Parkin substrates other than VDAC1.